Inovasi Layanan Cetak Tiket Mandiri Untuk Menunjang Kualitas Pelayanan Publik - Noora Fithriana; Salome Silmia (Universitas Islam Malang, 2020)
Self-Printing Ticket has been fulfilling innovation criteria as it is able to adjust a new service. The Self-Printing Ticket innovation made by Indonesian Railways Company and applied in many Indonesian central stations is an effort to improve service quality of printing a train ticket. The aims of this research was to find out the Self-Printing Ticket innovation for supporting public service quality in Malang Station, along with supporting and obstructing factors of such innovation implementation. To reach the research aims, this research used qualitative method. Primary data of this research was got from (1) interviewing informants consisting of Head of Station, Head of Commercial Service Sub-Affairs, Customer Services, and service users of Self-Printing Ticket; (2) documentation; and (3) observing service room. Secondary data was taken from documents of Indonesian Railways Company. Of the research results, found out that the machine of Self-Printing Ticket was Yogyakarta Station Team innovation winning an annual event of Indonesian Railways Company. Based on the six service standards, the service innovation of Self-Printing Ticket in Malang Station was well applied so that it can support public service quality. Supporting factors of the service were facilities; where the obstructing factors were internet or server disruptions, power outage, jammed printer, and prospective passengers misunderstanding on the machine usage and their mistake in inputting the book code.